Nano-size effects on optical, structural and phononic properties of VO2 and WO3 by ultrasonic-nebulizer spray pyrolysis technique - Mwakikunga, Bonex Wakufwa (My University, 2007)
This dissertation presents for the first time the conditions for the synthesis of VO2 by ultrasonic nebula-spray pyrolysis (UNSP) from a precursor solution of NH4VO3+VCl3 optimized as follows: a carrier gas of argon at a flow rate of 11 liters per minute, a furnace temperature of 400 to 700oC. This work also incorporates thermodynamic variables of Tpr-P-V into the equations that relate the mean diameter of droplets, D, to frequency of the exciting ultrasound waves, f, the density of the precursor solution, and the surface tension, , previously worked on independently by Lang and Jokanovic. The incorporation results in the diameters of the droplets (and consequently the collected grains) being smaller as p and Tpr are increased in a non- linear form. The variable V, however, increases the diameter of the droplets as it is allowed to increase. This study shows the departures many authors find of the theory from experiment but it also shows that the departure does not lie in the equations but rather on post- synthesis and annealing effects. From X-ray diffraction, scanning electron microscopy (SEM) and Raman spectroscopy, this study shows that as furnace temperature is increased the morphology of the sample surfaces for both VO2 and WO3 transforms from amorphous to crystalline, from spherical grains to plate-like structures, with grain mean diameter increasing non-linearly in some cases and decreasing non-linearly in other cases confirming previous findings, the latter enjoying the majority vote. In Raman spectra of the as- obtained WO3, asymmetric broadening of the Raman peaks was observed in some samples and a phonon confinement model was employed in the size distribution prediction. These findings prompted the re- workout of the phonon confinement model. In this dissertation an equation has been derived based on the Faucet-Campbell equation of the PC model. The new equation relates the ratio of neighboring peaks in a material’s Raman spectrum to the mean diameter of the grains. The present modification allows the PCM model to predict the grain size beyond the current limiting range of 0 to 100 nm. Analysis of the experimental data using this equation unveils two different equations- one for particles of size below 100 nm and the other equation for particles with larger that 100 nm. Also this analysis has enabled the present study to evaluate the phonon dispersion relations for WO3.
Student Number : 0420699F - MSc Dissertation - School of Physics - Faculty of Science
Keywords: ultrasonic; pyrolysis; vanadium dioxide; tungsten trioxide